Marriage Practice in Contemporary Nepal - Khatri, Bal Krishna (NUTA Journal, 2021)
Marriage is one of the oldest universal micro social institutions which are established by human society as an essential social structure for gaining more benefit in the social and functioning aspects. It provides the legal rights of regular sexual intercourse, producing of the offspring socially, religiously and legally. It is one of the ways to transfer an inheritance of the property in our societies. This belief is influenced by Hinduism which regards marriage as the important custom or sacrament. Although, the perception and practices of marriage is not universally accepted which varies across societies and culture, i.e., cross cousin marriage practices are common among Gurung, Magar and Tamang ethnic groups. Levirate marriage can be found in Tamang ethnic group which is not acceptable in another caste. Arrange marriage is one of the most popular form and also practices of marriage in contemporary Nepal whereas child marriage, capture marriage and forced marriage has been already prohibited by law. Experimental marriage, Group marriage and Companionate marriage are not existed. Most of the people have been hearing and conducting the marriage but the proper acceptable definition is not found till date. It is no doubt that marriage is an inevitable social institution but the practice may be different in different places. Main objectives of this article are briefly highlighting the various thought and forms of marriages which have practiced in different caste and place of Nepal by using primary and secondary sources.